Assessment on Qualitative Research in Language Education: Perspectives from Thesis Supervisors - Suherman, Andri; Nazri, M. Adib; Surayya, Siti Ayu (Prodi Pendidikan Bahasa Inggris, FPBS, Universitas PGRI Semarang, 2025)
This study aims to examine assessment strategies employed by thesis supervisors in assessing their students qualitative research, and to explore the thesis supervisors’ perceptions of their assessment strategies. Conducted in an Indonesian university, this study adopted an explanatory sequential design of mixed-research by using a purposive sampling technique to recruit ten thesis supervisors as the research participants. The findings showed that the supervisors made a total of 1,002 feedback comments on the 20 thesis drafts. The feedback comments focused on five different aspects of students’ theses including research components (58.98%), coherent and cohesion (22.32%), grammatical accuracy (10.27%), vocabulary used (4.49%), and reference and citations (3.89%). Meanwhile, data gained from interview sessions revealed four dominant themes in supervisors’ perceptions of their assessment strategies including instructional scaffolding, time efficiency, students’ engagement, and researcher independence. Despite some limitation such as limited number of participants and inadequate research instruments, this study provides pedagogical implication including the necessity to facilitate students with relevant trainings to help improve their thesis writing skills. Suggestions for future research are also presented.